Acute Cerebellitis and Hydrocephalus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Two children, a girl aged 5 years and a boy aged 11 years, with acute cerebellitis, tonsillar herniation and hydrocephalus are reported from Schneider Children's Medical Center of Israel, Petah Tikva, Tel Aviv.